REVERSAL EVIDENCE POLICY ON CORRUPTION AS SPECIALIZATION OF CRIMINALIZATION - Benny Sumardiana (Indonesian Journal of Criminal Law Studies, 2017)
Corruption is an extraordinary crime, because corruption happens in all areas of life, and has been done systematically, accordingly extraordinary action is required. To overcome with the occurrence of various type of corruption that required a special strategy. In this article, the authors use normative juridical approach method, that is by doing observation and then review and analyze secondary data in the form of legal materials, especially primary law materials and secondary legal materials. The collected data, both qualitatively and quantitatively, is further classified according to the data types. After that, the results of the study are arranged in a systematic and coherent manner, using problem studies that are specific to take the basics of general knowledge. The conclusion will be drawn in response to the issues that raised in this paper. The legislation that has been regulated the reverse evidence of corruption is considered to be ineffective, in several regulation about corruption, only gratification acts that embrace pure inverse evidence, while others are not purely adherent, whereas the effectiveness of the system of reversal of the burden this evidence is very good if it can be implemented properly and based on strict rules, the problem that concerned in this study is, the contradiction between the presumption of innocence principle and the presumption of guilt principle underlying this evidentiary system. The ideal concept offered in this study is, with the renewal in the setting of the eradication of corruption, and ultimately embraces the reversal of the burden of evidence purely in the corruption trial by considering the concept of equilibrium.